Notch inhibitor can attenuate apparent diffusion coefficient and improve neurological function through downregulating NOX2-ROS in severe traumatic brain injury - Zhang HM; Chen W; Liu RN; Zhao Y (Dove Medical Press, 2018)
Hong-Mei Zhang,1,2 Wei Chen,3 Rui-Ning Liu,1 Yan Zhao1 1Emergency Center, Zhongnan Hospital of Wuhan University, Wuhan 430071, Hubei, People’s Republic of China; 2Emergency Department, The Second Medical College of Jinan University, Shenzhen People’s Hospital, Shenzhen 518020, Guangdong, People’s Republic of China; 3Department of Intensive Care Unit, Taihe Hospital, Hubei University of Medicine, Shiyan 442000, Hubei, People’s Republic of China Introduction: Secondary brain injury is a major factor that affects the prognosis and outcome of traumatic brain injury (TBI) patients. Secondary brain edema is considered to be an initiating factor in secondary brain injury after TBI. A previous study has indicated that Notch signaling activation contributes to neuron death in mice affected by stroke; however, its role in neuronal oxidation stress for brain edema after TBI is not well established. Apparent diffusion coefficient (ADC) values can represent the brain edema after TBI. Methods: We established a rat model of acute craniocerebral injury, using functional MRI to evaluate the ADC and cerebral blood flow values. The present study was designed to determine the effect of Notch inhibitor DAPT upon oxidation stress for brain edema after TBI. Rats were randomly distributed into five groups, control group, severe TBI group, severe TBI + vehicle group, severe TBI + DAPT group, and severe TBI + DPI group. All rats were sacrificed at 24 hours after TBI. Results: Our data indicated that Notch signaling inhibitor DAPT significantly reduced the ADC values and improved the neurological function after TBI. In addition, DAPT decreased NOX2 levels and the ROS levels. Furthermore, DPI can decrease NOX2 levels and ROS levels.Conclusion: This study indicated that DAPT Notch signal inhibitors can inhibit NOX2-ROS generation, reduce the ADC values, relieve cerebral edema, and improve nerve function. Keywords: traumatic brain injury, secondary brain injury, apparent diffusion coefficient, Notch, cerebral blood flow